Determinasi Disiplin, Kompensasi dan Mutasi Terhadap Kinerja Pegawai - Zatul Akmam; Muhammad Hanafi (STIA Indragiri, 2017)
ABSTRACTThis study aims to identify and analyze the determination of discipline, compensation and mutations one at the same time the performance of employees in the Office of Legislative Secretariat Batam. This study uses three independent variables, discipline, compensation and mutation with one dependent variable namely performance. Usages of variables in this study is expected to know how is the process that occurs and what are the factors driving the creation of a good performance in the Parliament Secretariat Batam. These samples included 66 people who are employees at the Parliament Secretariat Batam.Samples were taken by sampling techniques. Data analysis method used is quantitative analysis, the validity, reliability test, classic assumption test, test multikoloniaritas, heterocedasticity test, normality test, multiple linear regression analysis, t-test, f, test the coefficient of determination R2. Keywords: Discipline, Compensation, and Performance mutation.